Exploring the 15-minutes city: the metropolitan context of Oporto - Cecília Silva; Marcelo Altieri; João Filipe Teixeira (U.Porto Journal of Engineering)
It is easy to understand why the idea of a 15-minutes city, providing most everyday amenities within 15-minutes travel time, has become so appealing to city officials and citizens in the last decades, and with particular strength, in the last few years following the COVID-19 pandemic. The explicit reduction of both travel distance and time are, in themselves, tantalizing for societies in need of coping with major challenges, such as, global warming, sustainable development, car-dependent cities, lack of quality urban spaces, and quality of life. Regardless, such prescriptive strategy seems to be at odds with less dense urban environments found in sprawl, the majority of suburban development and even some urban centres.